X-Ray Layered Refocusing Imaging Based on Linear Scanning - Bin Liu; Yue Luo; Ke Li; Xia Zhao (IEEE Photonics Journal, 2020)
In the process of X-ray digital imaging, due to the mutual occlusion of object structures of different depth layers, the image projection information is overlapped. X-CT(Computed-Tomography) and X-CL(Computed-Laminography) are usually used to obtain structural information of objects at different depths, but they are limited by accurate multi-dimensional motion control systems, complex scanning methods and poor real-time computing performance.To solve the problems, this paper proposed a method of X-ray layered imaging based on linear scanning. This method only needs the object to pass through the detection area along a straight line to realize the multi-view imaging, extracts the effective multi-view images information for refocusing imaging, and realizes the reconstruction of different depth layers of the object. Meanwhile, the automatic marking matting algorithm is employed to remove the non-focused interference in the refocused images. Experiments of X-ray layered imaging were conducted, which demonstrated the proposed method can achieve objects reconstruction with different depths, and effectively remove the non-focused interference.